â€œBokashi Effect of Fertilizer on the Growth Of Rice Production Methods and SRI (System Of Rice Intensification)â€ - Arnoldus Londong; Saartje Sompotan; Pemmy Tumewu; Jelly V. Porong (Universitas Sam Ratulangi, 2016)
ABSTRACTThis study aims to memgetahui Bokashi fertilizer influence on the growth and production of rice using the SRI (System Of Rice Intensification) held at the Village Taratara the West Tomohon sub district for 5 months from July to December 2014. The study used randomized block design with treatment A (5 ton Bokashi / ha), B (10 ton Bokashi / ha), C (15 ton Bokashi / ha), D (20 ton Bokashi / ha) and repeated 4 times to obtain 16 experimental plots. Data were analyzed by analysis of variance followed by LSD (Least Significant Difference) at 5% level.The results showed that the use of Bokashi fertilizer to increase rice production SRI method. Dose of 15 ton / ha of fertilizer bokhasi provide the highest SRI method of paddy production.Keyword: Bokashi, peddy,SRI Method (System Of Rice Intensification)